Pelatihan Kehumasan Dan Kerja Sama Di Indonesia - Misbah Fikrianto (AMMA : Jurnal Pengabdian Masyarakat, 2024)
Competency development is an effort made to improve the quality of human resources. Intensive competency improvement is carried out to provide added value to something that is done. Public Relations and Cooperation Training is a need for institutions and human resources, especially in government institutions. SEAMEO QITEP In Language together with the Riau Islands Provincial Teacher Mobilization Center carried out public relations and cooperation training from 18-20 April 2024 in Batam City. This activity was attended by around 60 participants, consisting of elements from the SEAMEO Centre in Indonesia, the Center for Teacher Mobilization, the Education Service, and public relations practitioners. At the start, the need to receive this training was 75%. After training, participants receive an increase in competency and benefits of 95%. This activity aims to increase competence in the field of public relations and cooperation in Indonesia. All participants gave positive responses to this training and provided recommendations for continuing the training. The organizing committee will provide continued support and development for this activity. Participants get benefits from building cooperation to increase the competence of teachers, education staff, human resources in the field of Public Relations, and Collaboration Teams.